Managing human resources toward achieving knowledge management - Yahya, Salleh; Goh, Wee‐Keat (Emerald, 2002)
This research examines the linkages between human resource management and knowledge management. Specifically, the association between four areas of human resource management (training, decision‐making, performance appraisal, and compensation and reward) with the five areas of knowledge management (knowledge acquisition, knowledge documentation, knowledge transfer, knowledge creation, knowledge application) is explored. The statistical results suggest that a knowledge organisation requires a different management approach than the non‐knowledge organisation. Hence, the role of human resource management is also unique. In terms of employee development, the focus should be placed on achieving quality, creativity, leadership, and problem solving skill. The design of a compensation and reward system should be on promoting group performance, knowledge sharing, and innovative thinking. The performance appraisal must be the base of evaluation of employee’s knowledge management practices, and an input for directing knowledge management efforts.